“Factores de riesgo materno asociados a hemorragia clínica post-parto vaginal en el hospital de apoyo N° 2 Yarinacocha – Pucallpa periodo 1993 – 1998” - Águila valles, Hellen Hevelin Del (1999)
The present study of case control longitudinal with collection retrospective of data was made in the Hospital of support N ° 2 Yarinacocha-Pucallpa, during those years ' of 1993 to 1998; for the purpose of detenninar the risk factors associated with hemorrhage postpartum vaginal. Our displays of study was confonnada by 167 patients with hemorrhage and 167 patients for the group control which totaled 334 patients, of which is reviewed thoroughly their respective stories clinical. After conducting the analysis, we found that the average blood loss is 725.15 ce the factors predisposing Associates A hemorrhage postpartum were: before PREGNANCY: maternal age